The Role of Local Government in the Process of the Brownfield Regeneration – Case Study of Košice , Slovakia - Džuňová, Jana; Douša, Milan; Koreňová, Darina (Review of European and Comparative Law, 2024)
Many enterprises were created during the process and steps of societal changes related to industrialization. Currently, we are undergoing further development and again changes, during which the established enterprises have been closed, and unused spaces have been left behind. The issue of brownfields is increasingly becoming more and more relevant. It is in everyone’s interest to use the potential of any area at the highest possible level. Brownfields offer several opportunities for overall revitalization using existing buildings. The main aim of this article is to analyze the status and possibilities of revitalizing brownfields in the city of Košice from a local government perspective. It also includes an optimal global model that covers the basic elements of subprocesses necessary for the local government’s revitalization of brownfields. The research results illustrate that identifying these objects generates a wealth of new information useful in understanding the current state of brownfields in Košice. This new knowledge can subsequently contribute to the quality of public administration’s public space management, the redevelopment of urban sites, and the improvement of urban life for everyone.